Medial septum glutamatergic neurons modulate nociception in chronic neuropathic pain via projections to lateral hypothalamus - Fan, Bing-Qian; Xia, Jun-Ming; Chen, Dan-Dan; Feng, Li-Li; Ding, Jia-Hui; Li, Shuang-Shuang; Li, Wen-Xian; Han, Yuan (Frontiers in Pharmacology, 2023)
Abstract The medial septum (MS) contributes in pain processing and regulation, especially concerning persistent nociception. However, the role of MS glutamatergic neurons in pain and the underlying neural circuit mechanisms in pain remain poorly understood. In this study, chronic constrictive injury of the sciatic nerve (CCI) surgery was performed to induce thermal and mechanical hyperalgesia in mice. The chemogenetic activation of MS glutamatergic neurons decreased pain thresholds in naïve mice. In contrast, inhibition or ablation of these neurons has improved nociception thresholds in naïve mice and relieved thermal and mechanical hyperalgesia in CCI mice. Anterograde viral tracing revealed that MS glutamatergic neurons had projections to the lateral hypothalamus (LH) and supramammillary nucleus (SuM). We further demonstrated that MS glutamatergic neurons regulate pain thresholds by projecting to LH but not SuM, because the inhibition of MS-LH glutamatergic projections suppressed pain thresholds in CCI and naïve mice, yet, optogenetic activation or inhibition of MS-SuM glutamatergic projections had no effect on pain thresholds in naïve mice. In conclusion, our results reveal that MS glutamatergic neurons play a significant role in regulating pain perception and decipher that MS glutamatergic neurons modulate nociception via projections to LH.